Exacerbation of chronic obstructive pulmonary disease: discussion of controversies. A review - Andrey A. Zaytsev (ZAO "Consilium Medicum", 2023)
The paper discusses the controversial issues of infectious exacerbation of chronic obstructive pulmonary disease. Researchers and practitioners share a common understanding of rational patient management, which involves the evolution of exacerbation terminology, the impact of viral infection and air pollutants, the significance of biomarkers, and the appropriate antibiotic therapy regimens. Clinical reflections on the current causes of chronic obstructive pulmonary disease exacerbations and modern therapeutic options are presented.